2013
DOI: 10.3109/0886022x.2013.828261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spectrum of peripheral neuropathy in predialysis patients with chronic kidney disease

Abstract: Our data suggests that NCV testing when complimented with meticulous neurological assessment can provide invaluable input. These tests apart from helping us detect neuropathy in advanced renal dysfunction; can also detect the disease in largely asymptomatic patients which avoids the necessity to order for detailed neurophysiological investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 20 publications
4
45
1
2
Order By: Relevance
“…In study we focused on peripheral neuropathy, but there are other studies (Doreen, 2011) on primarily axonal sensorimotor polyneuropathy and they noted that peripheral neuropathy occurs in 50-60% of patients who require hemodialysis. In our patients, we use clinical examination to detect peripheral neuropathy , and we found 50 of 80 patients were having peripheral neuropathy (62.5%), of which 39 were diabetics (78%) and 47 were hypertensive (94%), and we found similar results in other studies (Aggarwal, 2013) Result:-Peripheral neuropathy was diagnosed using the previously mentioned methods and the results came as the following: Out of 80 patients of renal failure, which were on hemodialysis, 50 patients were having peripheral neuropathy (62.5%) , of which 39 were diabetics (78%) and 47 were hypertensive (94%). Out of 42 female patients, 29 were affected (58% ) and out of 38 male patients 21 were affected (42%).…”
Section: Discussion:-supporting
confidence: 77%
“…In study we focused on peripheral neuropathy, but there are other studies (Doreen, 2011) on primarily axonal sensorimotor polyneuropathy and they noted that peripheral neuropathy occurs in 50-60% of patients who require hemodialysis. In our patients, we use clinical examination to detect peripheral neuropathy , and we found 50 of 80 patients were having peripheral neuropathy (62.5%), of which 39 were diabetics (78%) and 47 were hypertensive (94%), and we found similar results in other studies (Aggarwal, 2013) Result:-Peripheral neuropathy was diagnosed using the previously mentioned methods and the results came as the following: Out of 80 patients of renal failure, which were on hemodialysis, 50 patients were having peripheral neuropathy (62.5%) , of which 39 were diabetics (78%) and 47 were hypertensive (94%). Out of 42 female patients, 29 were affected (58% ) and out of 38 male patients 21 were affected (42%).…”
Section: Discussion:-supporting
confidence: 77%
“…Additionally, a case of accelerated uremic neuropathy with excellent improvement after dialysis was reported [23]. Moreover, peripheral neuropathy has been described in pre-dialysis patients with CKD [24]. CTS, with prevalence rates ranging from 6 to 31 %, has been described as the most common mononeuropathy [11,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 97%
“…Regardless, there is increasing evidence of demonstrable peripheral neuropathy related to CKD in contemporary pre‐dialysis CKD and population‐based cohorts. Two small studies have recently shown that peripheral neuropathy is present in 70% GFR stages 3 and 4 CKD cohorts, of which one excluded patients with diabetes . Further evidence of the impact of CKD on the pathogenesis of peripheral neuropathy was recently highlighted in a population‐based cohort of 908 people that identified evidence of kidney disease as an independent risk factor for abnormal lower limb nerve conduction results .…”
Section: Implications Of Peripheral Neuropathy In Ckdmentioning
confidence: 99%
“…Peripheral neuropathy affects 60–90% of dialysis patients and has long been recognised in patients with advanced CKD . More recently, both population‐ and CKD‐specific studies have demonstrated evidence of peripheral neuropathy in earlier stages of CKD . Given the prevalence and impact of peripheral neuropathy in CKD, there is a pressing need for targeted treatment strategies.…”
Section: Introductionmentioning
confidence: 99%